Pituitary adenoma in patients with multiple endocrine neoplasia type 1: a cohort study. Issue 6 (26th November 2021) - Le Bras, Maelle; Leclerc, Hélène; Rousseau, Olivia; Goudet, Pierre; Cuny, Thomas; Castinetti, Frederic; Bauters, Catherine; Chanson, Philippe; Tabarin, Antoine; Gaujoux, Sebastien; Christin-Maitre, Sophie; Ruszniewski, Philippe; et al.
Abstract : Objective: Pituitary adenoma (PA) is one of the three major components of multiple endocrine neoplasia type 1 (MEN1). Recent studies have suggested that MEN1-associated PAs are less aggressive than initially estimated. We propose an analysis of the outcome of PAs with a standard of care treatment in a nationwide cohort of MEN1 patients. Design: Retrospective observational nationwide cohort study using the MEN1 patient registry from the French Group of Endocrine Tumours (GTE). Methods: The GTE database population consists of 1435 patients with MEN1. This analysis focused on 551 patients recruited after 2000 with at least 3 years of follow-up. The study outcome was tumour progression of PA defined by an increase in Hardy classification (HC) during follow-up according to referring physician regular reports. Results: Among 551 MEN1 patients (index and related), 202 (36.7%) had PA, with 114 (56.4%) diagnosed by MEN1-related screening. PAs were defined according to HC as microadenoma (grade I) in 117 cases (57.9%), macroadenoma in 59 (29.2%) with 20 HC grade II and 39 HC grades III–IV and unspecified in 26 (12.8%). They were prolactinomas in 92 cases (45.5%) and non-secreting in 73 (36.1%). After a median follow-up of 3 years among the 137 patients with HC grades I–II, 4 patients (2.9%) presented tumour progression. Conclusion: PAs in patients with MEN1 are less aggressive than previously thought. Tumour progression is rare with a standard of care monitoring and treatment, especially in related patients who mostly present non-secreting microadenoma. MRI monitoring for asymptomatic MEN1 patients should be reduced accordingly.